Genotypic Frequency of RHC Antigen in Women of Reproductive Age in Pakistan - Bashir, Saima; Akhtar, Fahim; Naeem, Mohammad Abdul; Khan, Maria; Tashfeen, Sunila; Khan, Saleem Ahmed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the genotypic frequency of RHC antigen in females of reproductive age. Study Design: Cross-sectional study. Place and Duration of Study: Armed Forces Institute of Transfusion (AFIT) and Pak Emirates Military Hospital, (PEMH) in collaboration with NUMS Pakistan, from Dec 2020 to Dec 2021. Methodology: Females aged 16 to 45 years were recruited in the study. Demographic data, including age, parity, ethnicity etc.,was recorded on a proforma. Venous blood samples were collected in EDTA tubes, and DNA was extracted using 5% Chelex TM. A conventional Polymerase chain reaction and amplified products were subjected to Polyacrylamide Gel electrophoresis. Results: Amongst 200 females, 172(86%) had the expression of RHC antigen, while 28(14%) were negative for the respective antigen. These results were valuable in predicting the risk of hemolytic disease in fetuses and newborns and alloimmunization in our population. Conclusion: Females in the reproductive age group had RHC positivity of 86%. This data will help predict the risk of HDFN in future pregnancies and individuals at risk of alloimmunization in RHC-negative women.